Evil: A matter of Perspective - Rodríguez Durango, Pavel Eduardo (Disertaciones, 2023)
Discussing the idea of evil itself cannot be ignored its multiplicity of expressions. This article proposes to think about this concept from various dimensions of human endeavor, such as ethics, the weakness or strength of the human will, the idea of good, the praxis of evil, literary narratives, and the question about why our ability to commit injustices, of generating suffering in others, the nativism of evil within reason, the condition of human nature and its relationship with the achievement of one’s own desire, the meta/narrative that exposes the legitimacy or legality of the empire of violence and determines what is tolerable or not, from thinkers such as Saint Augustine, Machiavelli, Hobbes, Kant, Schopenhauer, Spinoza, Bataille, Arendt, among others, to deduce that finally, talking about evil requires reflecting on violence human decision to act against the good.